Sistem notasi tari rakyat melayu di semenanjung malaysia: kajian kes yayasan warisan johor dan jabatan kebudayaan & kesenian negara - Leng, Poh Gee (2022)
This thesis focuses on the development and the exercise of dance notation systems for Malay folk dance through the case studies of Yayasan Warisan Johor and the Jabatan Kebudayaan & Kesenian Negara. In the local dance studies, the literature related to dance notation is inadequate and this causes limitations on the understanding of the roles and functions of dance notation in promoting Malay folk dance. Through qualitative methodologies such as ethnography and movement structural analysis, this thesis identifies the various existing notation systems in peninsular Malaysia; and explains the importance of dance notation in conveying the structure and form of Malay folk dance. This thesis shows that notation systems created by YWJ and JKKN are the deliberate and flexible process in which the founders select and integrate various notation methods such as descriptions, illustrations and adaptations from Labanotation in order to record and preserve the repertoires of zapin and tarian gubahan baharu from InspiTari. This thesis suggests that the notation systems combining symbols and terminology is the most appropriate for transcribing Malay folk dance.